Analisis Kemampuan Bertanya Siswa Pada Mata Pelajaran Tematik di SDN 60 Kota Bengkulu - Irfan Supriatna (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Questioning is a primary part of student learning activities. Questioning activity is asking factual or hypothesis question that begin with guidance from teacher until the student understand themselves and become habitual activity.This research aims to describe Student Questioning Ability in Environment is Our Friend Theme of Environmental Conservation Movement Sub Theme of Thematic Subject and describe the obstacle experienced by the student of 5th Grade 60 Bengkulu City Elementary School year 2019/2020. The method used in this study is qualitative descriptive approach, that is why this research emphasize the processes rather than results. Subjects in this research are 18 students of 5th Grade 60 Bengkulu City using observation and interview sheet instruments. Data collection techniques used were observation, interviews and documentation.The result of this research is there are 7 students who have fulfill all questioning ability indicator requirements, on the other hand there is one student who only achieve one point from the requirements, two requirements of questioning ability indicators fulfill by 6 students, there are two students who can’t fulfill any requirement of questioning ability indicators. Obstacles experienced by students have not been able to use Indonesian language correctly, lack focus in asking, lack of confidence, afraid of being wrong, embarrassed when laughed by their friend and unable to raising the voice so the question can reach the entire class. Conclusion of the research is every student student of 5th Grade 60 Bengkulu City have different questioning ability.